2019
DOI: 10.1007/s40430-019-1667-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection strategy and load on the performance of a common-rail diesel engine fueled with Jatropha curcas biodiesel–diesel blend

Abstract: The present work attempts to determine the optimal engine load, fuel injection pressure (FIP), start of injection timing (SOI) and pilot-main injection intervals (PMII) regarding the performance and emissions of a diesel engine fueled with J20 biodiesel (20 vol% Jatropha curcas biodiesel + 80 vol% 0# diesel). A four-factor and three-level full factorial design and response surface methodology (RSM) were employed in the design of experiments and in the analysis of test results. All the models developed using RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Based on Xu et al [ 30 ] article's, it was concluded that 160 MPa of injection pressure, 4.02 degree CA at the start of injection, 65.71% loading conditions, and 4.4 degrees CA pilot to main injections produce higher thermal efficiency and lower CO, soot, HC, and NO emissions while using 20% jatropha oil biodiesel blended diesel fuel. “An addition of jatropha oil methyl ester with decanol and n‐propanol with combinations of 45:45:10, 40:40:20, 35:35:30 and 30:30:40 blending ratio in CI engine produces 4% hike in thermal efficiency, in‐cylinder pressure (ICP), and heat release rate (HRR).…”
Section: Introductionmentioning
confidence: 99%
“…Based on Xu et al [ 30 ] article's, it was concluded that 160 MPa of injection pressure, 4.02 degree CA at the start of injection, 65.71% loading conditions, and 4.4 degrees CA pilot to main injections produce higher thermal efficiency and lower CO, soot, HC, and NO emissions while using 20% jatropha oil biodiesel blended diesel fuel. “An addition of jatropha oil methyl ester with decanol and n‐propanol with combinations of 45:45:10, 40:40:20, 35:35:30 and 30:30:40 blending ratio in CI engine produces 4% hike in thermal efficiency, in‐cylinder pressure (ICP), and heat release rate (HRR).…”
Section: Introductionmentioning
confidence: 99%